Analysis Of Leverage And Managerial Ownership With Dividend Policy As A Moderating Variable On Stock Return - Nabella Rosa Anggun Pitaloka; Muhadjir Anwar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This finding examines the effect of leverage and managerial ownership on stock returns moderated by dividend policy in consumer goods companies listed on the IDX. The type of data in this study is quantitative data. Purposive sampling was used to create the sample, and 46 businesses that satisfied the pre-established sample requirements were included. Moderated Regression Analysis (MRA) is used as an analysis method.The results of the analysis state that Leverage can contribute to increasing Stock Returns, Managerial Ownership can contribute to increasing Stock Returns, Dividend Policy is not able to contribute to moderating the effect of Leverage on Stock Returns, Dividend Policy can contribute to moderating the effect of Managerial Ownership on Stock Returns in consumer goods companies on the IDX.